Shared space and resource use within a building environment: An indoor geography. - Villarreal, Mark; Baird, Timothy D.; Tarazaga, Pablo A.; Kniola, David J.; Pingel, Thomas J.; Sarlo, Rodrigo (Geographical Journal, 2025)
Indoor spaces are essential to most humans' lives. Furthermore, in many cases, buildings are shared indoor environments that contain diverse people and resources. Spatial patterns of use are important but under‐examined aspects of human‐building interactions. This study leverages perspectives from human‐environment geography and mechanical engineering to examine spatial patterns of use within a network of shared indoor spaces in an academic building at a research university in the United States. Here we ask: (1) What spaces and resources do building users value? and (2) How are values associated with observed measures of use? We hypothesise that spatial patterns of use follow an ideal free distribution (IFD), a common ecological model of resource use. To test this, we define measures of value and use derived from mixed qualitative (n = 50) and survey‐based social data (n = 196) and data from a building‐based system of accelerometers. Our analyses provide some support for the IFD hypothesis. We discuss the implications of this finding and potential new avenues for geographic research in shared indoor environments.